Mass, nutrients and dissolved organic carbon (DOC) lateral transports off northwest Africa during fall 2002 and spring 2003 - N. Burgoa; F. Machín; Á. Marrero-Díaz; Á. Rodríguez-Santana; A. Martínez-Marrero; J. Arístegui; C. M. Duarte (Ocean Science, 2020)
The circulation patterns and the impact of the lateral export of nutrients and organic matter off NW Africa are examined by applying an inverse model to two hydrographic datasets gathered in fall 2002 and spring 2003. These estimates show significant changes in the circulation patterns at central levels from fall to spring, particularly in the southern boundary of the domain related to zonal shifts of the Cape Verde Frontal Zone. Southward transports at the surface and central levels at 26∘ N are 5.6±1.9 Sv in fall and increase to 6.7±1.6 Sv in spring; westward transports at 26∘ W are 6.0±1.8 Sv in fall and weaken to 4.0±1.8 Sv in spring. At 21∘ N a remarkable temporal variability is obtained, with a northward mass transport of 4.4±1.5 Sv in fall and a southward transport of 5.2±1.6 Sv in spring. At intermediate levels important spatiotemporal differences are also observed, and it must be highlighted that a northward net mass transport of 2.0±1.9 Sv is obtained in fall at both the south and north transects. The variability in the circulation patterns is also reflected in lateral transports of inorganic nutrients (SiO2, NO3, PO4) and dissolved organic carbon (DOC). Hence, in fall the area acts as a sink of inorganic nutrients and a source of DOC, while in spring it reverses to a source of inorganic nutrients and a sink of DOC. A comparison between nutrient fluxes from both in situ observations and numerical modeling output is finally addressed.